Polymeric materials based on epoxy oligomer DER-331 and hardeners of different physical and chemical nature for repairing of gas production equipment - Sapronov, O. O.; Sotsenko, V. V.; Antonio, B.; Smetankin, S. O.; Yurenin, K. Yu. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2020)
The optimal content of PEPA and TETA hardeners and polymerization temperature during matrix formation on the basis of epoxy oligomer DER-331 were determined. The dynamics of dependence of hardener content on physical and mechanical properties of epoxy matrix was investigated. According to the results of the study, materials with the optimal content of hardener and temperature range of polymerization for the formation of a composition with high physical and mechanical properties and its further use for the repair of gas equipment are proposed. Developed polymeric materials containing the hardener TETA with a content of q = 8–10 weight parts per 100 weight parts of epoxy oligomer DER-331 are characterized by high physical and mechanical properties, in particular: the fracture stresses during the flexion are σfl = 80.0–95.1 MPa, the modulus of elasticity E = 2.8–2.9 GPa, impact strength W = 7.9–13.5 kJ/m2. The fracture structure of such composites is characterized by less deep branched chip lines with relatively uniform transitions, which makes it possible to state a slight stress state of the polymer, and hence its increased resistance to fracture.